Synergistic effects of organic fertilizer and corn straw on microorganisms of pepper continuous cropping soil in China. Issue 1 (1st January 2020) - Gao, Jingxia; Pei, Hongxia; Xie, Hua
ABSTRACT: Because of the large population, large demand, limited arable land and many environmental factors, continuous cropping have become a very common phenomenon in China. However, long-term continuous cropping has caused a series of serious soil-borne diseases, and the yield and quality of crops to drop, which seriously restricted the sustainable development of agricultural industry. Therefore, in order to improve the yield of pepper and reduce the occurrence of soil-borne diseases, it is essential to understand the effect of continuous cropping of pepper on soil microbial community composition and abundance. In this study, high throughput sequencing was used to study the effects of seven treatments of organic fertilizers and corn straw on soil microbial community and function of pepper continuous cropping. The results showed that the yield of all treatments was significantly higher than that of the control. The soil microbial diversity and community composition showed that Proteobacteria and Ascomycota were the most abundant phylum in all treatments. In conclusion, there were significant differences among the seven treatments and the treatment of fowl dung with corn straw was the best fertilizer combination to improve the yield and output value of pepper. Besides, the addition of fowl dung and corn straw not only can improve the community and functions of microorganisms, but also enhance the ability of disease resistance, and ultimately decrease the soil-borne diseases. The results will help to provide scientific basis for rational application of organic fertilizer and corn straw, and overcoming continuous cropping obstacles. Graphical Abstract: